DRCOG revision guide a guide to success in the new-style examination - Davies, Nigel (RCOG Press, 2008)
The DRCOG (Diploma) is an examination for doctors who wish to offer obstetrics, gynaecology and other aspects of women's health care in a primary care setting (GP surgeries, walk-in centres and family planning clinics). This book provides a comprehensive guide to the new style DRCOG examination which was introduced in October 2007. It includes: • an overview of the curriculum and syllabus • a guide to the format of the DRCOG examination • sample questions for each of the question formats: extended matching questions (EMQs), single best answer questions (SBAs) and multiple choice questions (MCQs) • six sample papers • answers to all of the sample questions and papers • tips for candidates.